THE IMPORTANCE OF NETWORKING AND COLLABORATION FOR MSMEs GROWTH CASE STUDY OF KHRISNA BALI SOUVENIR CENTER - Alamsyah, Eko; Sudarmiatin, Sudarmiatin; Wardana, Ludi Wishnu (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2024)
This article explores the importance of networking and collaboration in the growth of Micro, Small, and Medium Enterprises (MSMEs), focusing on a case study of Krisna Souvenir Center in Bali. MSMEs play an important role in creating jobs and driving local economic growth in Indonesia. This study shows how Krisna leverages its strong network with local craftsmen and farmers to improve product quality and market access. Through effective collaboration, Krisna has succeeded not only in increasing turnover, but also in driving product innovation that is attractive to consumers. These findings confirm that building a solid network is an important strategy for MSMEs to face market challenges and increase competitiveness. This article is expected to provide insight for other MSMEs in optimizing collaboration for sustainable growth. This study uses SMARTPLS4 analysis software with the PLS-SEM model, from the results of the analysis of all independent variables that are significant to the dependent variable, the Collaboration and networking variables, have an effect on Economic Growth with the Market Access Mediation variable. The research data is primary data obtained from the results of filling out the questionnaire that has been carried out by respondents with a sample size of 100 from the results of calculations using the Slovin formula